Effect of Posterior Horn Medial Meniscus Root Tear on In Vivo Knee Kinematics. Issue 7 (11th July 2014) - Marsh, Chelsea A.; Martin, Daniel E.; Harner, Christopher D.; Tashman, Scott
Background: Medial meniscus root tear (MMRT) is a recently recognized yet frequently missed meniscal tear pattern that biomechanically creates an environment approaching meniscal deficiency. Hypothesis/Purpose: The purpose of this study was to assess the effect of MMRT on tibiofemoral kinematics and arthrokinematics during daily activities by comparing the injured knees of subjects with isolated MMRT to their uninjured contralateral knees. The hypothesis was that the injured knee will demonstrate significantly more lateral tibial translation and adduction than the uninjured knee, and that the medial compartment will exhibit significantly different arthrokinematics than the lateral compartment in the affected limb. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Seven subjects with isolated MMRT were recruited and volumetric, density-based 3-dimensional models of their distal femurs and proximal tibia were created from computed tomography scans. High-speed, biplane radiographs were obtained of both their affected and unaffected knees. Moving 3-dimensional models of tibiofemoral kinematics were calculated using model-based tracking to assess overall kinematic variables and specific measures of tibiofemoral joint contact. The affected knees of the subjects were then compared to their unaffected contralateral knees. Results: Affected knees demonstrated significantly more lateral tibial translation than the uninjured contralateral limb in all dynamic activities. Additionally, the medial compartment displayed greater amounts of mobility than the lateral compartment in the injured limbs. Conclusion: This study suggests that MMRT causes significant changes in in vivo knee kinematics and arthrokinematics and that the magnitude of these changes is influenced by dynamic task difficulty. Clinical Relevance: Medial meniscus root tears lead to significant changes in joint arthrokinematics, with increased lateral tibial translation and greater medial compartment excursion. With complete root tears, essentially 100% of circumferential fibers are lost. This study will further our knowledge of meniscal deficiency and osteoarthritis and provide a baseline for more common forms of medial meniscal injuries (vertical, horizontal, radial), with various degrees of circumferential fiber function remaining.